1995
DOI: 10.1164/ajrccm.152.6.8520787
|View full text |Cite
|
Sign up to set email alerts
|

How common are renal angiomyolipomas in patients with pulmonary lymphangiomyomatosis?

Abstract: Pulmonary lymphangiomyomatosis has been associated with renal angiomyolipoma in case reports, but the prevalence of this association has not been well documented. The objective of this study was to determine the frequency of renal angiomyolipoma in a series of subjects with pulmonary lymphangiomyomatosis. Eighteen consecutive patients with pulmonary lymphangiomyomatosis were seen at a single institution between 1989 and 1994. Of these, one patient was excluded because she did not have an abdominal computed tom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0
4

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(62 citation statements)
references
References 23 publications
0
56
0
4
Order By: Relevance
“…Up to 63% of women with lymphangioleiomyomatosis also have renal angiomyolipoma (3,5). Angiomyolipomas are benign tumors consisting of smooth muscle cells, fibrous tissue, adipose tissue, and abnormally formed vascular channels (6).…”
Section: Introductionmentioning
confidence: 99%
“…Up to 63% of women with lymphangioleiomyomatosis also have renal angiomyolipoma (3,5). Angiomyolipomas are benign tumors consisting of smooth muscle cells, fibrous tissue, adipose tissue, and abnormally formed vascular channels (6).…”
Section: Introductionmentioning
confidence: 99%
“…The pathologic features of sporadic and TSC-associated pulmonary LAM are identical (10). Sixty percent of women with sporadic LAM have renal angiomyolipomas (11,12), leading to speculation that LAM and TSC are related diseases (13,14).…”
mentioning
confidence: 99%
“…But the cause and pathogenesis of LAMare not known yet. There is a significant overlap between LAM, angiomyolipoma, and the syndrome of tuberous sclerosis (14). It has been shown that the smooth muscle found in PLAMis similar histologically and immunohistochemically to that found in angiomyolipoma (1 1).…”
Section: Discussionmentioning
confidence: 99%